2016
DOI: 10.1039/c6dt01357k
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble Schiff base-actinyl complexes and their effect on the solvent extraction of f-elements

Abstract: Conventional solvent extraction of neptunyl(v), Cm(iii), Eu(iii) & uranyl(vi) by bis(2-ethylhexylphosphoric acid (HDEHP) can be altered through introduction of an actinyl selective hold-back complexant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Other studies on (Np V O 2 ) + Schiff base complexes typically see this band shift to ∼1000 nm. 20,69,80 However, we note that the use of H 2 salenSO 3 [N,N′-bis(5-sulfanatosalicylidene)] caused a rapid reduction from (Np VI O 2 ) 2+ to (Np V O 2 ) + , 80 whereas Np VI O 2 L(MeOH) displayed only a small amount of reduction to Np IV L 2 . It is also noted that the in situ reduction of Np VI O 2 L(MeOH) gave a spectrum nearly identical to that of a separate sample recorded 1 month after synthesis.…”
Section: Synthesis Of Npmentioning
confidence: 85%
“…Other studies on (Np V O 2 ) + Schiff base complexes typically see this band shift to ∼1000 nm. 20,69,80 However, we note that the use of H 2 salenSO 3 [N,N′-bis(5-sulfanatosalicylidene)] caused a rapid reduction from (Np VI O 2 ) 2+ to (Np V O 2 ) + , 80 whereas Np VI O 2 L(MeOH) displayed only a small amount of reduction to Np IV L 2 . It is also noted that the in situ reduction of Np VI O 2 L(MeOH) gave a spectrum nearly identical to that of a separate sample recorded 1 month after synthesis.…”
Section: Synthesis Of Npmentioning
confidence: 85%
“…In contrast, we have shown that an aqueous soluble Schiff-base ligand will complex NpO 2 2+ but rapidly reduce it to NpO 2 + . 27 Returning to the tBu-Salen-Np VI system in CH 3 CN, we observe vibrational progression bands between 540 and 650 nm. Such transitions are observed in this region for other Np VI complexes, e.g., [NpO 2 (CO 3 ) 3 ] 4−50 and NpO 2 Cl 2 in THF.…”
mentioning
confidence: 83%
“…23−25 In this context, we have previously reported on an aqueous soluble Schiff base that selectively coordinates UO 2 2+ and NpO 2 + in an aqueous phase, yielding separation from a range of trivalent f-element cations. 26,27 We report here synthetic, spectroscopic, crystallographic, and metal-ion-partitioning studies involving a tetradentate, lipophilic Schiff base, N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-ethylenediamine (tBu-Salen; Figure 1), and the hexavalent mid-actinides (UO 2 2+ , NpO 2 2+ , and PuO 2 2+ ).…”
mentioning
confidence: 99%
See 2 more Smart Citations